Meteo-climatic analysis during the period 1984 - 2014 in Rome area (Central Italy) - Conte, Giovanni; Del Bon, Andrea; Gafà, Rossella Maria; Martarelli, Lucio; Monti, Gennaro Maria (Acque Sotterranee - Italian Journal of Groundwater, 2015)
In this paper rainfall trends and a seasonal distribution model of the period 1984-2014 for the urban area of Rome and surroundings are presented using the available data of 46 rain gauge stations. The average annual precipitation is 793 mm in the urban area and increases up to 945 mm in the surrounding hilly areas. The seasonal distribution of the isohyets is almost homogeneous, increasing from plain towards hilly areas. The scattered variability of annual rainfall does not allow the recognition of trends and cyclic tendencies, with the exception of seasonal variations. Nevertheless, the rainfall analysis highlights an increasing trend in winter and, to a lesser significant extent, in summer, while a decreasing tendency characterizes autumns and, definitely less spring periods. The annual rainfall time series analysis show significant changes for 28% out of the 46 stations considered, i.e.: descending to ascending trends or increasing of average values concomitant to the absence of significant trends. The plots of three-monthly (seasonal) total rainfall values show, for most of the rainfall stations, a winter season characterized by a negative to positive tendency inversion around 1993. According to the qualitative classification of the Seasonal Index (SI), the study area sectors fall between the classes "uniform but with a clear wet season" (SI=0.20-0.39) and "fairly seasonal with a minor dry season" (SI=0.40-0.59).The analysis of the rainfall was further developed by spatial elaboration of long-term trends derived from the data analysis of the Standard Precipitation Index (SPI), aggregated at annual, semiannual and quarterly scale.The analysis of the temperature data of 21 stations for the period 1984-2014 highlighted that, generally, isotherms follow the topographic elevations and the existence of an area, coinciding with the metropolitan area of Rome, characterized by temperatures greater than those of the surroundings.